Juncus maroccanus Kirschner, a new record to the european flora - Rudner, Michael; Deil, Ulrich (Acta Botanica Malacitana, 2011)
Juncus maroccanus Kirschner, novedad para la Flora Europaea Palabras clave. Juncaceae, Península Ibérica, España, Estrecho de Gibraltar, dunas. Keywords. Juncaceae, Iberian Peninsula, Spain, Straits of Gibraltar, dunes.